The Development of Students’ Logical Thinking Skills Using Arduino as A Learning Utility in the Computer System Subject - Nusuki Syari'ati Fathimah; Tsabita Widya Septivani; Eka Fitrajaya Rahman; Wahyudin Wahyudin (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
Logical thinking skills play an important role in learning computer system subjects, especially in basic logic gates material. The purpose of this study was to examine the growth of students' logical thinking skills in the computer system subject using Arduino as a learning utility. In this research, a pre-experimental design with a pretest-posttest one-group design was implemented. The 30 students of class X-RPL in SMK Sangkuriang Cimahi are used as subjects in this study. A test with a logical thinking indicator was used to assess the pupils' logical thinking abilities. The indicators consist of the ability to think logically, give an argument, and draw a conclusion. Based on n-gain analysis, the result shows that the student’s ability in logical thinking was barely increased with a gain score of 0,214. More specifically, the application of Arduino has a bigger influence on the ability to think logically and give an argument than its influence on the ability to draw a conclusion.